Quality assessment in seven different apple varieties commercialized in Portugal - Tomislava Živić; Ana Rita F. Coelho; Ana Coelho Marques; Diana Daccak; Inês Carmo Luís; Cláudia Campos Pessoa; Fernando Lidon; Maria Manuela Silva; Manuela Simões; Paulo Legoinha; Fernando Henrique Reboredo (Emirates Journal of Food and Agriculture)
Seven commercially available apples varieties in Portugal (Jongold, Pink Lady, Reineta, Fuji, Gala, Golden and Granny) were analyzed for their physical and chemical properties. In this context, mineral content, height, weight, diameter, firmness, total solids soluble content, color, total lipids content and total protein content were carried out. Mineral content was assessed using X-ray fluorescence spectrophotometry in apples with and without peel, revealing significant differences between each variety. Moreover, there were significant differences between height, dry weight content, density, total soluble solids content, firmness, size, colorimetric parameter. Furthermore, significant differences were also observed in Fe, Ca, K, Cl and S content as well as protein and total lipid content. Additionally, Reineta variety emerged as the sweetest variety among the studied varieties and the study also revealed that the mineral content was higher in apples with peel compared to those without peel, highlighting the nutritional importance of apple skin.